1974
DOI: 10.1084/jem.139.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulatory Role of the Thymus in the Maturation of Immune Response in the Rabbit

Abstract: Rabbits thymectomized in early adulthood produced more antihapten antibody than sham-thymectomized controls after hyperimmunization with 2,4-dinitrophenyl bovine gamma globulin (DNP-BGG). The average associated constant of anti-DNP antibody produced by thymectomized animals was more than 10 times higher than that of the controls. Similar effects were obtained by extensive treatment of rabbits with antithymocyte serum (ATS) before and during the immunization with DNP-BGG. The results indicated that relative dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…However, Gershon and Paul [9] demonstrated that T cells indirectly influence the production of high affinity anti-hapten antibodies in response to immunization with hapten-protein conjugates. Furthermore, Taniguchi and Tada [31] stressed the direct action of T cells on antibody maturation with B cells which had already been selected by the antigen and were ready to proliferate and synthesize antibody with the destined affinity. Thus, it is reasonable to assume that antibody affinity reflects the properties of both antigen-stimulated B and T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gershon and Paul [9] demonstrated that T cells indirectly influence the production of high affinity anti-hapten antibodies in response to immunization with hapten-protein conjugates. Furthermore, Taniguchi and Tada [31] stressed the direct action of T cells on antibody maturation with B cells which had already been selected by the antigen and were ready to proliferate and synthesize antibody with the destined affinity. Thus, it is reasonable to assume that antibody affinity reflects the properties of both antigen-stimulated B and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The affinity of the antibody reflects the properties of B cells rather than those of T helper cells [16], but the helper cells still seem to have some influence on the alteration of the affinity of anti-hapten antibodies [9,18,30,31]. Injection of complete Freund's adjuvant or bacterial lipopolysaccharide (LPS) concomitantly with antigen results in a heightening of the affinity of serum antibody [20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Siskind and co-workers (5, 17i 18) and Harel et al (19) have shown that mere nonspecific modifications of the magnitude of antibody response by adjuvant and immunosuppressants do not significantly alter the affinity of the antibody produced in the rabbit, although a high degree of antigenic competition in guinea pigs does affect profoundly the affinity of the produced antibody (19,20). However, Taniguchi and Tada (21) reported that affinity of produced antibody in the rabbit is influenced by the carrier-specific T cells. They found that a relative depletion of T cells by surgical or chemical thymectomy caused a marked enhancement of antibody formation accompanied by a striking increase in antibody affinity.…”
Section: Suppression Of Relative Avidity Of Pfc For Hapten By Carriermentioning
confidence: 99%
“…Thus help and suppression are probably mediated by separate functional cell populations. Suppressor cells are shorter lived in the mouse (25) and the rabbit (26) and apparently decline faster after thymectomy than do helper cells. The elegant studies of Cantor and Boyse (27) indicate that different antigens exist on helper and suppressor populations.…”
mentioning
confidence: 99%